PERKAWINAN EKSOGAMI RANG PADA MASYARAKAT DESA INELIKA, KECAMATAN BAJAWA KABUPATEN NGADA, NUSA TENGGARA TIMUR - Cun Bay, Timoteus (Humanis, 2015)
Marriage is a transitional period in human life. Ngada society’s marital system in Inelika village based rang (social strata) that are inherited form generation to generation. Over the times, where rang existence changed so that there was marital exogamy rang. The aim of this research is to explore the ideal marriage of Ngada society in Inelika village, the patterns of endogamy and exogamy marriage rang, and the implications and the factors that influence marital exogamy rang. The data used in the this study is qualitative data with the primary and secondary data source. The theory used in this study is the structural functional theory of Talcot Parson,s is well known paradigm of four functions, namely AGIL and Robert K. Merton’s theory of real functions (manifest) and the function hidden (latent).The concepts of this research is, marriage, exogamy rang, and marital exogami rang. Ngada society’s ideal marriage in Inelika village is endogamy rang and this revealed in the phrase buri peka naja logo bei ube. The process of marital endogamy rang namely, papa moni tewe nenu, and zeza. Marital exogamy rang in Inelika village is influenced by media technology factors, the absence of cultural transmission, and a shift in values and norms in society. Marital exogamy has impliclations for the rigts and obligation of the people in the Ngada society in Inelika village.
Keywords: Marriage, Exogamy Rang, Marital Exogamy Rang